-10+6x-3x=23

Simple and best practice solution for -10+6x-3x=23 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -10+6x-3x=23 equation:


Simplifying
-10 + 6x + -3x = 23

Combine like terms: 6x + -3x = 3x
-10 + 3x = 23

Solving
-10 + 3x = 23

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '10' to each side of the equation.
-10 + 10 + 3x = 23 + 10

Combine like terms: -10 + 10 = 0
0 + 3x = 23 + 10
3x = 23 + 10

Combine like terms: 23 + 10 = 33
3x = 33

Divide each side by '3'.
x = 11

Simplifying
x = 11

See similar equations:

| 6(2x+7)=7(6x+6) | | 9s+8=4s+13 | | 2c+8=a | | 2(x+7)/3= | | x=y^2+11y | | sen^2x=2senx | | 19x^2+12x=32 | | 6x+2+8x+4=90 | | (x-10)+(x+5)+x=180 | | 4+3(5x+14)=-39x-24 | | 5x^2-x=-9 | | x+4-=11 | | 6(x+1)=2(x+7) | | 7g-25=52 | | 1=5+x-x | | 4b-24=5b+15 | | -2(6+3y)-4(y-5)=-4y+2y | | 8y-6=10 | | 45=4k+13 | | -t-4=5 | | Log[9](x)+log[9](8x-1)=1 | | 6y-1=17 | | 18x-5(2x-2)=-21x+3 | | 6(j+3)=66 | | -2x-12=2x+4 | | 2(3x-7)=3x+5+5 | | 3=2x^3+3x | | (8r+3)-(7r+1)=6 | | 6(-3+5y)+3y=3(y-6) | | 96=8(w+6) | | a-b-7c=p | | 79+2y=180 |

Equations solver categories